Implications of number-space synesthesia on the automaticity of numerical processing. - Gertner, L; Henik, A; Reznik, D; Cohen Kadosh, R (2013)
Number-space synesthetes visualize numbers in specific spatial configurations. Their spatial-numerical perceptions are assumed to be automatic in nature and have been found to affect performance in various numerical tasks. The current study tested whether synesthetic number-space associations can modulate the well-established Size Congruency Effect (SiCE), which is considered to be an indication for the automaticity of numerical processing. Two groups, number-space synesthetes and matched controls, were tested on a numerical Stroop task (Henik and Tzelgov, 1982). In separate blocks, participants were presented with two digits and asked to make comparative judgments regarding either numerical values (numerical comparison) or physical size (physical comparison). Both dimensions were manipulated orthogonally, creating three congruency levels: congruent (e.g., 2 7), incongruent (e.g., 2 7) and neutral (e.g., 2 2 and 2 7 for physical and numerical blocks, respectively). For the numerical block, both synesthetes and controls showed the classic SiCE, indicating similar automatic processing of physical magnitude. However, in the physical block, synesthetes showed a lack of automatic numerical magnitude processing when the numbers to be compared were presented incompatibly with their relative position on the synesthetic number-form. This finding strongly suggests that synesthetes' number-space perceptions affect their ability to automatically process the semantic meaning of numerals. The involvement of space in automatic magnitude processing for number-space synesthetes and non-synesthetes is discussed.